Analisis Kepuasan Nasabah Menggunakan Metode Service Quality dan Customer Satisfaction Index - Kesumawati, Ramadini; Hendry, Hendry (Building of Informatics, Technology and Science (BITS), 2022)
Bank is a business entities that have the function of collecting funds and distributing them from and for the community. The service of a bank is said to be good not only from bank’s point of view, but also from customer’s opinion as a service user. The problem that occurs is when bank has not been able to meet good and appropriate service standars, resulting in customers feeling dissatisfied. This study aims to analyze customer satisfaction to find out how the quality of service is available and to help provide information regarding what steps should be taken to improve service quality Service Quality method and Customer Satisfaction Index. The stages in this research include surveys, literature studies, preparation and distribution of questionnaires, validity and reliability tests, gap analysis and percentage of satisfaction levels, writing results, and finally conclusions. The results show that there are 15 attributes with negative gap values and a satisfaction percentage of 80,38%. Based on these results, customers are satisfied with the service provided